2009
DOI: 10.1002/ijc.24638
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of microRNA expression in colorectal cancer

Abstract: In the last years, microRNAs (miRNA) have emerged as new molecular players involved in carcinogenesis. Deregulation of miRNAs expression has been shown in different human cancer but the molecular mechanism underlying the alteration of miRNA expression is unknown. To identify tumor-supressor miRNAs silenced through aberrant epigenetic events in colorectal cancer (CRC), we used a sequential approach. We first identified 5 miRNAs down-regulated in patient with colorectal cancer samples and located around/on a CpG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
323
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 408 publications
(347 citation statements)
references
References 36 publications
18
323
0
6
Order By: Relevance
“…Previous studies have shown extensive epigenetic silencing of one or several of the miR-9 genes in cancer (Lehmann et al, 2008;Lujambio et al, 2008;Omura et al, 2008;Bandres et al, 2009;Hsu et al, 2009). This silencing was common in tumor tissue, whereas nearly absent in normal tissue.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Previous studies have shown extensive epigenetic silencing of one or several of the miR-9 genes in cancer (Lehmann et al, 2008;Lujambio et al, 2008;Omura et al, 2008;Bandres et al, 2009;Hsu et al, 2009). This silencing was common in tumor tissue, whereas nearly absent in normal tissue.…”
Section: Discussionmentioning
confidence: 89%
“…However, the differences between the methylation statuses of miR-9-1 and miR-9-3 are clearly evident utilizing these specimens. Hypermethylation of the two hsa-miR-9 genes has been shown to be even more evident in tumors with lymph node metastases in colon, lung, breast and melanoma cancers (Lujambio et al, 2008;Bandres et al, 2009). In our ccRCC tumor samples, this was also observed with patients developing a recurrence having a higher occurrence of methylated miR-9-1 and miR-9-3 in their primary tumor compared with those who have not at time of analysis (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the enormous research efforts of the last decade promise major discoveries and novel implementation relative to potential treatments for CRC that will hopefully be available within the next 10 years. New findings implicating mutations in metastasis suppressor genes [1] or in known oncogenic pathways such as KRAS, BRAF, PTEN, IGFR1 and EGFR [2-4] as well as epigenetic alterations involving DNA methylation dysregulation and/or chromatin remodeling [5] and miRNA control of gene expression [6] have greatly expanded the knowledge of how metastatic dissemination proceeds. The constant interplay between the tumor and its surrounding microenvironment continuously modifies their synergistic mechanisms and responses generally to the tumor's advantage, such that attacking the lesions on all fronts becomes a necessity.…”
mentioning
confidence: 99%